IDDF2019-ABS-0157 Fecal microbiota transplantations reconstitute gut fungal and viral microbiota in graft-versus-host disease. (7th June 2019) - Zhang, Fen; Yeoh, Yun Kit; Zuo, Tao; Cheng, Frankie; Tang, Whitney; Cheung, Kitty; Yang, Keli; Liu, Qin; Cheung, Chun Pan; Mo, Chow Chung; Hui, Mamie; Chan, Francis; et al.
Abstract : Background: Fecal microbiota transplant (FMT) has emerged as a potential treatment for severe colitis associated with graft-versus-host disease (GvHD) following hematopoietic stem cell transplant. Bacteria engraftment has been reported, however, the fate of fungi and viruses and their relationship with treatment response after FMT remains unclear. Here we report for the first time longitudinal dynamics of the gut mycobiome and virome in a teenager with gut GvHD successfully treated with multiple FMTs. Methods: A 14-year-old boy with severe life-threatening grade-4 gut aGVHD, refractory to corticosteroids and biologic therapies, were treated with a total of four FMTs. FMTs were conducted by duodenojejunal infusion from two different donors. Fecal samples were collected at baseline and up to 120 days after FMT. Combined DNA extraction of fecal bacteria and fungi was performed, followed by ultra-deep metagenomics sequencing and profiling of bacteriome and fungome . Fecal virus-like particles were enriched from feces and followed by metagenomics sequencing on VLP DNA as well as profiling of virome. Clinical phenotype and outcome were assessed and correlated with microbial profiles. Results: FMT altered the gut bacterial, fungal and viral communities simultaneously in the GvHD patient, and resulted in recovery of the patient. Bacterial diversity was gradually restored after each FMT, engraftment of donor-derived fungi occurred instantly after a single FMT and persisted up to 4 months, whilst viral diversity was improved after multiple FMTs but the composition varied substantially over time. Moreover, FMT reduced an overrepresented fungus Fusarium oxysporum (61.4% at day 0 vs 0.5% at day 120) and virus Torque teno virus (98.8% at day 0 vs 0.5% at day 120) in the patient in parallel with substantial increase in the bacterial, fungal diversity and the abundance of Caudovirales bacteriophages . In addition, Serial FMTs enhanced the ecological network of bacteria-fungi interactions in the recipient with a significant increase in these inter-kingdom correlations after each FMT. Conclusions: We show that bacterial, fungal and virus communities respond differently to FMT. In addition to bacteria, future FMT practice should account for the significance of reconstituting gut fungi and viruses.